Manajemen Strategi Pembelajaran dalam Membentuk 9 Pilar Karakter di Playgroup MILAS - Anaas Ridlo Yuliana; Aflaha Rara Wurinta (PG-PAUD Trunojoyo, 2020)
This study aims to analyze the learning strategies management in forming the 9 Pillars of character in the MILAS Playgroup Yogyakarta. The subjects of this study were the principal and educators. Data collection has done by observation and interview methods. After that, the data validity test was carrying out by means of triangulation. Then the data analysis technique has done by data reduction, data presentation, and conclusions or verification. The results showed that the 9 pillars of character through the learning strategies management learning strategies departing from vision and mission to evaluation. The learning strategies applied to create the 9 pillars of character in the MILAS playgroup are: (1) Love of God and the universe and its contents, (2) Responsibility, Discipline, and Independence, (3) Honesty, (4) Respect and Courtesy, (5) ) Compassion, Concern, and Cooperation, (6) Confidence, Creative, Hard Work, and Never Give Up, (7) Justice and Leadership, (8) Good and Humility, and (9) Tolerance, Peace Love, and Unity.